RAD51 deficiency disrupts the corticospinal lateralization of motor control - Cécile Gallea; Traian Popa; Cécile Hubsch; Romain Valabrègue; Vanessa Brochard; Prantik Kundu; Benoît Schmitt; Éric Bardinet; Eric Bertasi; Constance Flamand‐Roze; Nicolas Alexandre; Christine Delmaire; et al. (2013)
Mirror movements are involuntary symmetrical movements of one side of the body that mirror voluntary movements of the other side. Congenital mirror movement disorder is a rare condition characterized by mirror movements that persist throughout adulthood in subjects with no other clinical abnormalities. The affected individuals have mirror movements predominating in the muscles that control the fingers and are unable to perform purely unimanual movements. Congenital mirror movement disorder thus provides a unique paradigm for studying the lateralization of motor control. We conducted a multimodal, controlled study of patients with congenital mirror movements associated with RAD51 haploinsufficiency (n = 7, mean age 33.3 ± 16.8 years) by comparison with age- and gender-matched healthy volunteers (n = 14, mean age 33.9 ± 16.1 years). We showed that patients with congenital mirror movements induced by RAD51 deficiency had: (i) an abnormal decussation of the corticospinal tract; (ii) abnormal interhemispheric inhibition and bilateral cortical activation of primary motor areas during intended unimanual movements; and (iii) an abnormal involvement of the supplementary motor area during both unimanual and bimanual movements. The lateralization of motor control thus requires a fine interplay between interhemispheric communication and corticospinal wiring. This fine interplay determines: (i) the delivery of appropriate motor plans from the supplementary motor area to the primary motor cortex; (ii) the lateralized activation of the primary motor cortex; and (iii) the unilateral transmission of the motor command to the limb involved in the intended movement. Our results also unveil an unexpected function of RAD51 in corticospinal development of the motor system.